Growth and Nutrient Use Efficiency in Terminalia arjuna Bedd. Seedlings Grown in Various Potting Mixtures - Srivastava, Neeta; Behl, H. M. (Indian Forester, 2002)
Seedlings of Terminalia arjuna grown in different potting media were identified for superior quality. Growth biomass, leaf area and nutrient uptake were studied. The treatments consisted of four potting media:sand (T1), sandy loam soil (T2 ), alkaline soil mixed with sand, 4: 1 (T3) and soil as in T3 with additional amendment of farm yard manure, 4: 1 : 1 (T4). Seedlings grown in sand (T1 ) showed a poor performance and improved in T3 and T4 producing seven to eight times greater biomass compared to T1 and T2 treatments. There was a significant (P < 0.05) increase in seedling height, diameter and leaf area in T3 and T4 media compared to other treatments.Differences in seedling biomass and leaf area between T3 and T4 treatments were not significant. Leaves of seedlings grown in FYM amended medium had highest chlorophyll and protein content. Similarly, seedlings in this treatment showed increased uptake of Nand Fe compared to other treatments, however, it was not found to be critical in early stages of seedling growth and therefore uptake of these nutrients may be considered as luxury consumption since difference in seedling biomass between T3 and T4 was not significant. T. arjuna seedlings showed a high nitrogen use efficiency even in nutrient poor soil media, thus exhibiting a higher plasticity. These seedlings appear to be tolerant to sodic soil conditions FYM amendment was not found critical in growth promotion 180 days seedlings growth as it enhanced growth and nutrient uptake only to limited extent which was statistically insignificant.